Geotecnologias para a gestão pública: uma aplicação em Icapuí/CE - Santos, Ana Maria Ferreira dos (2014)
This research presents the Geotechnology as instrumentation capable of making more efficient public management. The municipality of Icapuí was the local scenario chosen for the implementation of the proposal. Aiming to show that systematized information and spatially referenced through the thematic cartography, and representation of information systems, contribute positively to the public administration, during the development of the thesis, was built and published the Atlas of Icapuí, and designed the geographic information System – GIS for the municipality. Cartography was prepared through the manual vectorization of images with a resolution of 50 cm, detail, enabling plotting of thematic maps of the municipality as a whole, and communities, in enlarged scales. The scales of maps produced vary between 1:5,000 and 1:150,000. SRTM data were used for the altimetrics data acquisition and generation of MDT, and the Geology and Geomorphology were represented on the basis of the interpretation of images and in studies developed by MEIRELES & SANTOS (2011), dealing with the geomorphological evolution of the coastal plain of Icapuí. The thesis that the Geotechnologies configure important tooling for the public administration, sought to highlight, through cartography produced and GIS, the coastal ecosystems, sectors in erosive process, areas of potential risk, appropriate urban expansion areas, preservation areas, and identify interventions that lead to loss of biodiversity and the conservation actions that can help in the recovery of degraded environments.